2014
DOI: 10.1111/ijcs.12106
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with financial independence of young adults

Abstract: Family economic factors such as parental income, stock holding, and financial assistance decreased the level of young adults' financial independence. Additional analyses indicated that the level of financial independence of college graduates was higher than those who had never attended college or were currently in college, but did not differ from those who had dropped out of college. Common and different factors associated with young adults' financial independence were also identified among the four education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 47 publications
6
101
0
Order By: Relevance
“…We found the benefits of financial self‐efficacy to be evident even after we accounted for the effects of both financial education and a participant's annual income, and this finding is in line with previous research showing that, beyond socioeconomic factors, financial self‐efficacy contributes to financial stability (e.g., Xiao, Chatterjee, and Kim ) while financial knowledge contributes to financial self‐efficacy (e.g., Serido, Shim, and Tang ; Xiao et al 2014). It may be, as Lim et al () argues, that young adults who believe they are financially capable will also be more willing to seek out the information or assistance they need in order to meet new challenges, and since other studies focused on the financial self‐efficacy of college students agree on this point, it seems reasonable to assume that the number of student‐loan defaults occurring annually might be reduced if the financial education provided at the time that a student loan is offered were to emphasize suggested plans and heuristics for repaying student loans.…”
Section: Discussionsupporting
confidence: 91%
“…We found the benefits of financial self‐efficacy to be evident even after we accounted for the effects of both financial education and a participant's annual income, and this finding is in line with previous research showing that, beyond socioeconomic factors, financial self‐efficacy contributes to financial stability (e.g., Xiao, Chatterjee, and Kim ) while financial knowledge contributes to financial self‐efficacy (e.g., Serido, Shim, and Tang ; Xiao et al 2014). It may be, as Lim et al () argues, that young adults who believe they are financially capable will also be more willing to seek out the information or assistance they need in order to meet new challenges, and since other studies focused on the financial self‐efficacy of college students agree on this point, it seems reasonable to assume that the number of student‐loan defaults occurring annually might be reduced if the financial education provided at the time that a student loan is offered were to emphasize suggested plans and heuristics for repaying student loans.…”
Section: Discussionsupporting
confidence: 91%
“…Quantitative research has revealed a relationship between parental resources and students' reported financial independence. Xiao et al (2014) found that students whose parents had higher incomes and assets were less likely to report financial independence than those with lower levels; in a similar vein, -Walker et al (2012) found that parents with the lowest income levels, who provided the least financial support to their student children, were more likely to consider their child to be an adult. Thus, a lack of financial support encouraged, if not forced, young people into taking on adult characteristics such as financial independence.…”
Section: Parental Contributions and Financial (In)dependencementioning
confidence: 87%
“…Being young can be described as the vulnerable transition period from childhood to adulthood, from being protected by parents to becoming independent (Frønes & Brusdal, ). In consumer societies, this transition period certainly also implicates becoming more financially independent and responsible as a consumer (Brusdal & Berg, ; Xiao et al, ). Young people are debutants in many—often complex—markets, and therefore expected to be particularly vulnerable in the consumer role (Berg, a, ; Hall, ).…”
Section: Background For This Studymentioning
confidence: 99%